2003
DOI: 10.1007/s00011-003-1206-4
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of I?B kinase, BMS-345541, blocks endothelial cell adhesion molecule expression and reduces the severity of dextran sulfate sodium-induced colitis in mice

Abstract: This represents the first example of an inhibitor of IkappaB kinase with anti-inflammatory activity in vivo and indicates that inhibitors of IkB kinase show the promise of being highly efficacious in inflammatory disorders such as inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
31
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 9 publications
5
31
0
Order By: Relevance
“…Wedelolactone, on the other hand, was only active at concentrations >20 μmol/L. This order of potency is in broad agreement with the previously reported efficacy of the four compounds at inhibiting IKK (12,26,35,38) and suggests that they exert their antiproliferative and apoptotic effects by suppressing IKK activity. To investigate this hypothesis further, we conducted a number of experiments to examine activation of key components of the NF-κB pathway in W256 cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Wedelolactone, on the other hand, was only active at concentrations >20 μmol/L. This order of potency is in broad agreement with the previously reported efficacy of the four compounds at inhibiting IKK (12,26,35,38) and suggests that they exert their antiproliferative and apoptotic effects by suppressing IKK activity. To investigate this hypothesis further, we conducted a number of experiments to examine activation of key components of the NF-κB pathway in W256 cells.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we studied the effects of four commercially available agents that have previously been reported to inhibit IKK activity (12,26,35,38) on proliferation and migration D, mRNA expression of uPAR, PTHrP, MMP9, and vascular endothelial growth factor in W256 as measured by rt-PCR followed by quantitative PCR. Columns, means of three independent experiments; bars, SD.…”
Section: Discussionmentioning
confidence: 99%
“…These results help to reconcile apparently discrepant information from prior reports on the role of NF-B in controlling intestinal inflammation (11,12). Thus, mice selectively deficient for IKK␤ in IECs exhibit more severe acute colitis (13) and epithelial loss of IKK␥ caused spontaneous colitis (14), supporting the notion that IEC IKK␤ and NF-B have an important protective role that prevents injury-induced mucosal inflammation.…”
Section: Discussionsupporting
confidence: 66%
“…Inhibition of IKK␤ suppresses the production and secretion of the prototypic proinflammatory cytokine TNF-␣ and attenuates disease in animal models of rheumatoid arthritis, inflammationinduced bone loss, and allergen-induced airway disease (6)(7)(8)(9). Furthermore, inhibition of NF-B by either antisense oligonucleotides directed against RelA/p65 or a small-molecule inhibitor of IKK␤ appeared to ameliorate disease in mouse models of intestinal inflammation (10)(11)(12), suggesting that NF-B-directed therapy could be a valuable novel strategy in IBD therapy. In sharp contrast, however, conditional ablation of IKK␤ in intestinal epithelial cells (IECs) caused increased inflammation in an acute, chemically induced colitis model (13) and loss of IKK␥ in IECs caused spontaneous colitis (14).…”
mentioning
confidence: 99%
“…Peroral administration of BMS-345541 inhibits serum TNF-␣ production following LPS injection in a dose-dependent manner (19). Additional studies support the use of BMS-345541 as a selective NF-B inhibitor and anti-inflammatory agent, including findings of reduced joint inflammation and destruction in a collagen-induced arthritis model, reduced severity of colitis in a dextran sulfate sodium-induced colitis model, and improved graft survival in a murine model of cardiac graft rejection (22,26,27). In our experiments, we found that when administered before LPS, BMS-345541 treatment decreased NF-B activation and neutrophilic lung inflammation measured at 8 h. Subsequently, we treated mice with BMS-345541 during the period when NF-B activity was differentially up-regulated in the LPS pump model to investigate whether attenuation of NF-B activation would convert this model of lung injury to one of transient inflammation.…”
Section: Discussionmentioning
confidence: 96%